Unraveling Prostate Tumorigenesis through CRISPR-Cas9: A Functional Genomics Insights from Cell and Animal Models (Feni University Journal, 2026)
Prostate cancer is still one of the most common cancers to be identified in males, and it still takes an alarming number of lives annually [28]. Castration-resistant prostate cancer (CRPC) is the clinical form that presents the biggest therapeutic challenge since it frequently develops ways to avoid hormone deprivation and other conventional treatments [18], [3]. The introduction of CRISPR/Cas9 gene-editing technology has changed how scientists study the biology of prostate cancer within the last ten years [7],[l3]. CRISPR now functions as a scalpel and a microscope, allowing researchers to examine important factors like androgen receptor signalling and noncoding RNAs that affect the development of tumours [1], [4], [35]. Researchers have found novel factors that contribute to medication resistance by utilising CRISPR for functional genomic screening. One such factor is the protein PTGES3, which is important for the regulation of androgen receptors [20]. Despite these encouraging developments, it is still difficult to translate laboratory results into treatments that are ready for patients. In addition to more general ethical concerns about genome editing, researchers still have practical challenges in resolving off-target mutations, the genetic variety of tumours, and the safe delivery of CRISPR components [9], [5], [35]. Future developments in delivery systems, simultaneous gene editing, and the integration of CRISPR with immune therapy provide hope for more individualised and successful treatments for prostate cancer. [31], [15].FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (269-288)